METHODS FOR DETERMINING LEADERSHIP QUALITIES AND ABILITIES IN STUDENTS - J.Zaynobidinov (World Scientific Research Journal, 2025)
Annotation.  In this article, students have identified those who are capable of management, forming leadership qualities in the process of their activities. The group is empirically based on the qualities of leadership that are manifested in the educational process, which is the leading activity of students in the conditions, as well as in the conditions of mutual cooperation.